2021
DOI: 10.3390/polym13223878
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Glycyrrhizic Acid and ZnO/Palygorskite on Improving Chitosan-Based Films and Their Potential Application in Wound Healing

Abstract: The synergistic effect of chitosan (CS), glycyrrhizic acid (GA) and ZnO/palygorskite (ZnO/PAL) as potential wound dressing was evaluated in the form of films by the solution casting method. The nanocomposite films were well-characterized with ATR-FTIR, XRD and SEM to explore the interactions between CS, GA and ZnO/PAL. Physical, mechanical and antibacterial properties of the nanocomposite films were systematically investigated for their reliability in end-up utilization. Importantly, it was found that the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 79 publications
(86 reference statements)
0
3
0
Order By: Relevance
“…In publications [ 46 , 47 ] biocomposite chitosan-based films modified with ZnO NPs were prepared that were active against wound-present pathogens, i.e., E. coli , S. aureus , K. pneumoniae , B. subtilis . The work [ 46 ] dealt with the analysis of a film based on chitosan (mol. weight 800 kDa), glycyrrhizinic acid and ZnO NPs/palygorskite nanorods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In publications [ 46 , 47 ] biocomposite chitosan-based films modified with ZnO NPs were prepared that were active against wound-present pathogens, i.e., E. coli , S. aureus , K. pneumoniae , B. subtilis . The work [ 46 ] dealt with the analysis of a film based on chitosan (mol. weight 800 kDa), glycyrrhizinic acid and ZnO NPs/palygorskite nanorods.…”
Section: Resultsmentioning
confidence: 99%
“…In manuscript [ 48 ], the authors developed a wound dressing on the basis of cotton pads and a biocomposite consisting of chitosan, glycogen and 30–80 nm ZnO NPs. Contrary to publications [ 46 , 47 ], in [ 48 ] the healing effect of the material was studied as compared to sterile gauze. A fast and almost complete healing of back wounds in the Wistar rats was demonstrated (males weighing 180–200 g), as well as excellent epithelization, granulation, tissue generation and collagen deposition.…”
Section: Resultsmentioning
confidence: 99%
“…The results of this paper also proved that GA immensely improved the survival rate of CLP rats in a dose-dependent manner and effectively inhibited their systemic inflammatory response and the growth of bacteria in rat blood. An antibacterial study showed that the growth of Gram-positive Staphylococcus aureus could be completely inhibited by GA; besides, Zhang et al found that chitosan, GA, and ZnO/palygorskite could supply a broad-spectrum antibacterial activity by the agar diffusion method [ 26 , 27 ]. In short, GA had antibacterial and anti-inflammatory effects on experimental sepsis rats.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, chitosan/bentonite films possess several qualities suitable for use in exudative wound dressings. Zhang et al [135] developed chitosan/glycyrrhizic acid/ZnO/palygorskite films for treating skin wounds. The films exhibited light transmittance, barrier properties (including water content, water solubility, and swelling degree), improved mechanics, and thermal stability.…”
Section: Wound Dressingmentioning
confidence: 99%